Synthesis, Biological Activity and Molecular Modeling of 4-Fluoro-N-[ω-(1,2,3,4-tetrahydroacridin-9-ylamino)-alkyl]-benzamide Derivatives as Cholinesterase Inhibitors - Szymański, P.; Markowicz, M.; Bajda, M.; Malawska, B.; Mikiciuk-Olasik, E. (Arzneimittelforschung, 2012)
The aim of this study was to synthesize and determine the biological activity of new derivatives of 4-fluorobenzoic acid and tetrahydroacridine towards inhibition of cholinesterases. Compounds were synthesized in condensation reaction between 9-aminoalkyl-tetrahydroacridines and the activated 4-fluorobenzoic acid. Properties towards inhibition of acetyl- and butyrylcholinesterase were estimated according to Ellman’s spectrophotometric method. Among synthesized compounds the most active were compounds 4a and 4d. These compounds, in comparison with tacrine, were characterized by the similar values of IC50. Among all obtained compounds, 4d presented the highest selectivity towards inhibition of acetylcholinesterase. Molecular modeling studies revealed that all derivatives presented similar extended conformation in the gorge of acetylcholinesterase, however, there were 2 main conformations in the active center of butyrylcholinesterase: bent and extended conformation.
Keywords: Alzheimer’s disease; tacrine; fluorobenzoic acid; docking; Ellman’s method